The causes of stress among UiTM Campus Samarahan students / Nazara Junidin and Kemala Mustapa - Junidin, Kemala; Mustapa, Nazara (2011)
Stress in a term psychology and biology by endocrinologist lang systems first coined in the biological context in 1930 which has in more recent decades become a common places of popular palace. It refer to the consequence of the failure of an organism of human or animal to respond appropriately to emotional or physical threats actual or imagines.